The Influence of Entrepreneurship Education, Entrepreneurial Knowledge and Entrepreneurial Inspiration on Generation Z’s Entrepreneurial Intention - Sholihah, Khalifah; Wibowo, Agus; Dianta, Karunia (Jurnal USAHA, 2023)
This study aims to examine the effect of entrepreneurship education on students' entrepreneurial intentions, as well as examine the mediating role of entrepreneurial knowledge and entrepreneurial inspiration. This study uses primary data obtained from a sample of 192 students at SMAN 108 Jakarta. In addition, the analytical method used in this study is SEM-PLS analysis method. The findings of this study strengthen the study of the influence of entrepreneurship education both directly and indirectly through entrepreneurial knowledge and entrepreneurial inspiration on entrepreneurial intentions. In addition, it found direct and indirect effects of entrepreneurship education on entrepreneurial intentions through entrepreneurial knowledge and entrepreneurial inspiration. This research was limited to one school and with limited variables, there are entrepreneurship education, entrepreneurial knowledge, entrepreneurial inspiration and entrepreneurial intention. The findings of this study provide insight into increasing entrepreneurial intentions by increasing the effectiveness of learning entrepreneurship education in schools.